Antioxidant and antibacterial properties of different nypa fruticans fruit extracts - Abdul Muony, Nur Haizum; Md Zin, Noor Hasniza; Abdul Wahab, Widya; Zainun, Zuraida (2016)
Nypa fruticans has many functions and can treat many diseases. However, nypa is still categorized as underutilized plant. The fruits are hard and cannot be eaten when ripe. Instead of ignoring the ripe fruits, it is better to utilize this high potential natural medicine fruit for commercial purposes. Thus, this study aims to extract bioactive compounds and bioactive peptides from ripe nypa flesh using different methods and to test the extracts for antioxidant and antibacterial activities. Two test systems, namely total phenolic content (TPC) and DPPH free radical scavenging, were used for the antioxidant analysis. The antibacterial screening was carried out by disc diffusion method towards selected bacteria. For phenolic compounds extraction, water gave the highest yield with 14.87 ± 0.37 %. Then the yield obtained for bioactive peptides was 6.91 ± 0.78 % and the concentration was 4.20 ± 0.17 µg/µl. Meanwhile, for bioactive compounds, extraction using 50 % acetone was found to have significantly high levels of TPC (151.09 ± 0.84 mg GAE/ g DW sample) and antioxidant activity by having the lowest IC50 value (1.34 ± 0.10 mg/ml). From statistical analysis, there was a strong positive correlation between TPC and antioxidant activity (R = 0.986). Finally, all the four extracts were subjected to screening for their possible antibacterial activity. However, all the extracts produced no effect on all the tested bacteria. Overall, the results from this study showed that the flesh of ripe Nypa fruticans fruits extracts contain only antioxidant property which can be a reference for further study.